Early and late place cells during postnatal development of the hippocampus - Chenyue Wang; Hongjiang Yang; Shijie Chen; Cheng Wang; Xiaojing Chen (Nature Communications)
Abstract A proportion of hippocampal CA1 neurons function as place cells from the onset of navigation, which are referred to as early place cells. It is not clear whether this subset of neurons is predisposed to become place cells during early stages, or if all neurons have this potential. Here, we longitudinally imaged the activity of CA1 neurons in developing male rats during navigation with both one-photon and two-photon microscopy. Our results suggested that a largely consistent population of cells functioned as early place cells, demonstrating higher spatial coding abilities across environments and a tendency to form more synchronous cell assemblies. Early place cells were present in both deep and superficial layers of CA1. Cells in the deep layer exhibited greater synchrony than those in the superficial layer during early ages. These results support the theory that an initial cognitive map is primarily shaped by a predetermined set of hippocampal cells.